The Ethical Issues Confronting Managers in the Sport Industry - Hums, Mary A. (Journal of business ethics, 1999)
The sport industry is an extremely diverse industry, including segments such as professional sport, intercollegiate athletics, health and fitness, recreational sport and facility management. The industry is currently experiencing rapid growth and development, and as it grows, sport managers in the different segments encounter ethical issues which are often unique to each segment. This article examines the professional sport, intercollegiate athletics, health and fitness, recreational sport and facility management segments of the sport industry and discusses the various ethical issues facing managers in each of these segments.